Clinico pathological presentation of carcinoma of breast at tertiary care centre in Vindhya region, Rewa, Madhya Pradesh, India - Shrivastava, Neelesh; Gupta, Rachna; Gaharwar, A.P.S. (International Surgery Journal, 2016)
Background:Carcinoma breast is one of the most common cancer affecting women worldwide. In present study different factors based on one year of experience at tertiary centre in India was identified. Methods: This is a prospective analysis (2013-2014) of database from all surgical units of S.S. Medical College, Rewa, India. Results:The incidence of carcinoma (Ca) of breast was 25.83%, amongst the total admitted cancer patients. Peak incidence 31.4% was in the age range 41-50 years, with the mean age of 45.2 years. 98.5% were married and multiparous, rural, illiterate belonging to low socioeconomic status. Painful Breast mass in 54.2%, axillary swelling 50%, ulcers on the lump10%, nipple discharge in 8.5% were found in the patients. Right breast involved more than left, upper outer quadrant was most commonly involved (61.4%).Most of the patients of carcinoma breast presented in stage II 32 (45.7%) followed by 23 (32.8%) in stage III, 12 (17.1%) patients presented with stage IV diseases while only three (4.2%) patients in stage I disease. 70% patients underwent surgical management. Modified Radical Mastectomy (MRM) was the most frequently performed operative procedure contributing for 37 (75.51%) cases followed by simple mastectomy in 16.32% cases. In Histopathology examination, infiltrating ductal carcinoma was the most common type of carcinoma accounting for 80.7% patients. 71.42% patients received chemotherapy. Conclusions:Finally it is concluded from this study that Ca of breast is a most common malignancy of breast in females in India. Most patients present in the late stage of disease due to inadequate education, lack of awareness of the diseases, its complications and hesitancy to report a doctor early. The main treatment of Ca of breast is surgery and chemotherapy and/or radiotherapy to prevention of local or regional recurrence and metastasis that occur in the course of disease.